Optimizing Higher Education Performance Through Data Integration Using the Zachman Framework: A Case Study on LAM Infokom Accreditation Criteria - Abdul Jahir; Arif Mu'amar Wahid; Tri Titis Sufranto (Jurnal Nasional Teknologi dan Sistem Informasi, 2024)
This study explores the application of the Zachman Framework to enhance data integration in higher education, specifically targeting the LAM Infokom accreditation criteria. The research addresses the challenges faced by educational institutions in managing fragmented data systems, which hinder their ability to meet comprehensive accreditation standards. Utilizing a multi-phase methodology, the research incorporates a literature review, case analysis, and prototype development to develop a cohesive data integration model aligned with accreditation requirements. The Zachman Framework provides a structured approach to system integration, covering perspectives such as data types, processes, storage locations, personnel, timelines, and objectives. The proposed integration strategy emphasizes the use of Application Programming Interfaces (APIs), middleware solutions, and a centralized data warehouse to unify disparate data sources. These integration methods facilitate seamless data exchange across academic, financial, and administrative systems, promoting data consistency and accessibility. Additionally, a phased implementation plan is recommended, outlining specific tasks, resource allocation, and monitoring measures to ensure systematic system improvement. Key performance indicators and evaluation metrics are established to monitor the effectiveness of the integrated system in meeting accreditation requirements. The study highlights the importance of a robust data governance framework and the role of stakeholder engagement in overcoming technical and resource-related challenges. Ultimately, this research contributes a practical data integration blueprint for higher education institutions, offering a replicable model for achieving and maintaining accreditation compliance through structured data management and governance practices.